Respuesta :

Lenvy

Answer:

[tex]g) \left(5x-2\right)\left(3x+2\right)[/tex]

[tex]h)2\left(8a-9\right)\left(a-2\right)[/tex]

[tex]i)3\left(21n^2+42n+16\right)[/tex]

Step-by-step explanation:

Starting with g) [tex]15^2+4x-4[/tex]

Break the expression into group

[tex]=\left(15x^2-6x\right)+\left(10x-4\right)[/tex]

Now, Factor out [tex]3x[/tex] from [tex]15x^2-6x[/tex] which is now is [tex]3x(5x-2)[/tex]

Next, Facotr out [tex]2[/tex] from [tex]10x-4[/tex] which is now is [tex]2(5x-2)[/tex]

Thus,

[tex]=3x\left(5x-2\right)+2\left(5x-2\right)[/tex]

Factor common term 5x -2

[tex]\left(5x-2\right)\left(3x+2\right)[/tex]

-------------------------------------------------------------------------------------------------------------

Next we have [tex]h)16a^2-50a+36[/tex]

Factor out common term thus we have [tex]2(8a^2-25a+18)[/tex]

Factor again: [tex]8a^2-25a+18[/tex] now turn into [tex](8a-9)(a-2)[/tex]

[tex]=2\left(8a-9\right)\left(a-2\right)[/tex]

-------------------------------------------------------------------------------------------------------------

Lastly we have [tex]i)63n^2+126n+48[/tex]

Rewrite the following:

63 as 3 * 21

126 as 2 * 42

48 as 3 * 16

[tex]63n^2+126n+48[/tex]

Now cut out common term:

[tex]=3\left(21n^2+42n+16\right)[/tex]

-------------------------------------------------------------------------------------------------------------

~lenvy~

Answer:

(g)  [tex](5x-2)(3x+2)[/tex]

(h)  [tex](16a-18)(a-2)[/tex]

(i)  [tex]3(21n^2+42n+16)[/tex]

Step-by-step explanation:

To factor a quadratic in the form [tex]ax^2+bx+c[/tex]

  • Find 2 two numbers ([tex]d[/tex] and [tex]e[/tex]) that multiply to [tex]ac[/tex] and sum to [tex]b[/tex]
  • Rewrite [tex]b[/tex] as the sum of these 2 numbers: [tex]d + e = b[/tex]
  • Factorize the first two terms and the last two terms separately, then factor out the comment term.

Question (g)

[tex]15x^2+4x-4[/tex]

[tex]\implies ac=15 \cdot -4=-60[/tex]

[tex]\implies d+e=4[/tex]

Factors of 60:  1, 2, 3, 4, 5, 6, 10, 12, 15, 20, 30, 60

Therefore, the two numbers (d and e) that multiply to -60 and sum to 4 are:

10 and -6

Rewrite [tex]4x[/tex] as [tex]+10x-6x[/tex]:

[tex]\implies 15x^2+10x-6x-4[/tex]

Factories first two terms and last two terms separately:

[tex]\implies 5x(3x+2)-2(3x+2)[/tex]

Factor out common term [tex](3x+2)[/tex]:

[tex]\implies (5x-2)(3x+2)[/tex]

Question (h)

[tex]16a^2-50a+36[/tex]

[tex]\implies ac=16 \cdot 36=576[/tex]

[tex]\implies d+e=-50[/tex]

Factors of 576:  1, 2, 3, 4, 6, 8, 9, 12, 16, 18, 24, 32, 36, 48, 64, 72, 96, 144, 192, 288, 576

Therefore, the two numbers that multiply to 576 and sum to -50 are:

-32 and -18

Rewrite [tex]-50a[/tex] as [tex]-32a-18a[/tex]:

[tex]\implies 16a^2-32a-18a+36[/tex]

Factories first two terms and last two terms separately:

[tex]\implies 16a(a-2)-18(a-2)[/tex]

Factor out common term [tex](a-2)[/tex]:

[tex]\implies (16a-18)(a-2)[/tex]

Question (i)

[tex]63n^2+126n+48[/tex]

Factor out common term 3:

[tex]\implies 3(21n^2+42n+16)[/tex]

This cannot be factored any further.